2023
DOI: 10.1002/pamm.202200301
|View full text |Cite
|
Sign up to set email alerts
|

On the energy dissipation in confined concrete subjected to shear cyclic loading

Abstract: The establishment of a simple engineering rule for predicting the fatigue failure of concrete has been pursued over the past decades. An energetic approach to the matter seems to be an attractive option that many researchers have embraced. In the present work, the authors attempt to contribute to the establishment of such a rule. In particular, the energy dissipation of confined concrete subjected to shear cyclic loading is studied and quantified. For this purpose, a microplane fatigue model recently introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…It can be observed that there is a clear increment of the plastic energy dissipation, while the damage energy dissi- pation remains in comparison of the same order. Numerical studies previously presented by the authors in [12,13] consistently yield similar results, where the energy dissipation attributed to damage does not change as dramatically as the plastic energy dissipation for simulations of the same test setup under the same boundary conditions.…”
Section: Fatigue Behaviorsupporting
confidence: 71%
See 1 more Smart Citation
“…It can be observed that there is a clear increment of the plastic energy dissipation, while the damage energy dissi- pation remains in comparison of the same order. Numerical studies previously presented by the authors in [12,13] consistently yield similar results, where the energy dissipation attributed to damage does not change as dramatically as the plastic energy dissipation for simulations of the same test setup under the same boundary conditions.…”
Section: Fatigue Behaviorsupporting
confidence: 71%
“…by replacing ψN , utilizing the chain rule, operating as described in [12,13], and integrating the dissipation rates with respect to the pseudo time t, the resulting expression yields the total energy dissipation associated with a microplane in the normal direction:…”
Section: Evaluation Of Energy Dissipationmentioning
confidence: 99%
“…It should be noted that such limitations of the current formulations of the PF-CZM can be improved by incorporating plasticity with kinematic hardening and considering a different fatigue hypothesis that links the dissipative processes of damage and plasticity, as shown in [33,34,107,108]. That enables the accumulation of the plastic strains under constant amplitude cyclic loading, which is known as the ratcheting mechanism.…”
Section: Numerical Simulationsmentioning
confidence: 99%